Prevalence of Acute Appendicitis among patients with Acute Abdominal Pain in Surgical Emergency in 10-50 Years - Muhammad Zohaib Hassan, Yasir Arfat, Zahid Iqbal, Muhammad Zeeshan, Ansar Aslam, Muhammad Imran Khokhar (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Acute abdominal pain is one of the most common presentations in surgical emergency departments, with acute appendicitis being the leading surgical cause. Despite advances in diagnostic modalities, early diagnosis of acute appendicitis remains challenging, and delayed intervention can significantly increase morbidity and mortality. Determining the prevalence of acute appendicitis among patients presenting with acute abdomen and understanding age-related variations in clinical presentation are essential for improving diagnostic accuracy and patient outcomes. Objective: To determine the prevalence of acute appendicitis among patients presenting with acute abdominal pain in the surgical emergency department and to evaluate age-related differences in clinical signs and symptoms. Methods: This prospective cross-sectional study was conducted in the surgical emergency department of a tertiary care hospital from July 2021 to January 2022. A total of 400 patients aged 10–50 years presenting with acute abdominal pain were included. Patients were stratified into four age groups for prevalence analysis and further divided into two age groups (10–30 years and 31–50 years) for assessment of likelihood ratios of clinical signs and symptoms. Clinical evaluation, laboratory investigations, and imaging were performed as indicated. Patients with suspected acute appendicitis underwent appendectomy based on clinical judgment and Alvarado scoring. Histopathological examination was used as the diagnostic gold standard. Data were analyzed using SPSS version 20.0. Results: Out of 400 patients, 157 (39.25%) underwent appendectomy for suspected acute appendicitis. Histopathological confirmation was obtained in 132 cases (84.07%), with a negative appendectomy rate of 15.92%. Acute appendicitis was most prevalent in the 21–30-year age group (42.04%) and was more common in males (55.41%) than females (44.58%). Clinical signs and symptoms demonstrated higher diagnostic value in younger patients, with right lower quadrant pain showing a high positive likelihood ratio in patients aged 10–30 years. Conclusion: Acute appendicitis constitutes a significant proportion of acute abdominal pain presentations, particularly among young adults. Clinical manifestations are more pronounced and diagnostically reliable in younger patients. Early clinical recognition remains crucial to reduce unnecessary surgery and prevent complications. Keywords: Acute abdomen; Acute appendicitis; Prevalence; Likelihood ratio; Surgical emergency.